1997
DOI: 10.1177/074193259701800106
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes and Attributes of General Education Teachers Identified as Effective Inclusionists

Abstract: School principals and special education teachers identified general education teachers who were the most skilled at including students with disabilities in their classrooms. After 10 individuals identified by both principals and special educators were interviewed, seven themes emerged. These teachers (a) described their own personalities as tolerant, reflective, and flexible; (b) accepted responsibility for all students; (c) described a positive working relationship with special educators; (d) reported adjusti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
28
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 11 publications
3
28
0
Order By: Relevance
“…Teachers who rated themselves as successful with inclusive education had smaller classes (13-21 students) and fewer students with disabilities included in their classrooms (two to four; Smith and Smith 2000). Teachers in different grade levels also showed differences in their perceptions of inclusive education (Olson, Chalmers, and Hoover 1997), with elementary teachers reporting more positive perceptions of inclusive education than their secondary counterparts (Olson, Chalmers, and Hoover 1997). The type and severity of disability also have been shown to have different effect on teachers' perceptions of inclusive education.…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations
“…Teachers who rated themselves as successful with inclusive education had smaller classes (13-21 students) and fewer students with disabilities included in their classrooms (two to four; Smith and Smith 2000). Teachers in different grade levels also showed differences in their perceptions of inclusive education (Olson, Chalmers, and Hoover 1997), with elementary teachers reporting more positive perceptions of inclusive education than their secondary counterparts (Olson, Chalmers, and Hoover 1997). The type and severity of disability also have been shown to have different effect on teachers' perceptions of inclusive education.…”
Section: Introductionmentioning
confidence: 93%
“…Studies conducted in both Taiwan and the USA show that there is a positive relationship between general education teachers' perceptions of inclusive education and the influence of inclusive education on children (D'Alonzo, Giordano, and Vanleeuwen 1997;Hsieh and Wang 2002;Li 1996;Olson, Chalmers, and Hoover 1997). However, not every teacher has positive perceptions of inclusive education.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…For example, failure due to causes that teachers perceive as fixed, such as low levels of ability, may result in a high level of expectation that failure will occur, whereas fa i l u re due to unstable causes, such as a teach e r 's instructional methods, may lead to a high expectation that something can be done to modify the students' academic performance. Olson, Chalmers and Hoover (1997) found that the individualisation of expectations was a requisite for effective integrated services and that, when interviewed, teachers emphasised the need to set those expectations at a level that would produce achievement. In related research, Rolinson and Medway (1985) found some evidence that teachers are more likely to attribute success among children with special educational needs to their own efforts than to those of the children, whereas they attribute children's academic failures to the children rather than to themselves.…”
mentioning
confidence: 99%